2022
DOI: 10.3390/polym14214577
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Octavinyl Oligomeric Sesquisiloxane Nanomaterial-Modified Asphalt Using Molecular Dynamics Method

Abstract: This paper mainly studies the compatibility and properties of octavinyl oligomeric silsesquioxane nanomaterial (nano-OvPOSS)-modified asphalt, in comparison with those of traditional zinc oxide nanomaterial (nano-ZnO) and silica nanomaterial (nano-SiO2), through the method of molecular dynamics simulation. Nano-OvPOSS, an organic–inorganic nano-hybrid material, is studied for the first time in the application of asphalt modification. By studying different sizes and types of nanomaterials, this paper elucidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Likewise, a material that has been showing a high chance of success in improving aging resistance is zinc oxide-ZnO [15][16][17][18][19]. ZnO is a colorless material with low toxicity [20], showing a high compatibility with asphalt binders [21][22][23], high conductivity, heat capacity, and chemical-thermal stability [24]. It also exhibits a low ultraviolet-UV optical absorption and expansion coefficient [25].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a material that has been showing a high chance of success in improving aging resistance is zinc oxide-ZnO [15][16][17][18][19]. ZnO is a colorless material with low toxicity [20], showing a high compatibility with asphalt binders [21][22][23], high conductivity, heat capacity, and chemical-thermal stability [24]. It also exhibits a low ultraviolet-UV optical absorption and expansion coefficient [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects that motivate its use in binders and asphalt mixtures are as follows: (i) it is a material with high compatibility with asphalt and is stable at high temperatures [24][25][26];…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reutilized two types of waste plastic (polypropylene (PP) and polyethylene (PE)) as asphalt modifiers to improve the performance of asphalt pavements [4]. Feng et al found that nano-OvPOSS can be employed as a viable asphalt modifier to ensure a well-rounded performance of modified asphalt [5].…”
mentioning
confidence: 99%